Recent Advances in Technology Research and Education Proceedings of the 16th International Conference on Global Research and Education Inter-Academia 2017 - Luca, Dumitru; Sirghi, Lucel; Costin, Claudiu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents selected contributions to the 16th International Conference on Global Research and Education Inter-Academia 2017 hosted by Alexandru Ioan Cuza University of Iași, Romania from 25 to 28 September 2017. It is the third volume in the series, following the editions from 2015 and 2016.  Fundamental and applied research in natural sciences have led to crucial developments in the ongoing 4th global industrial revolution, in the course of which information technology has become deeply embedded in industrial management, research and innovation - and just as deeply in education and everyday life.   Materials science and nanotechnology, plasma and solid state physics, photonics, electrical and electronic engineering, robotics and metrology, signal processing, e-learning, intelligent and soft computing have long since been central research priorities for the Inter-Academia Community (I-AC) - a body comprising 14 universities and research institutes from Japan and Central/East-European countries that agreed, in 2002, to coordinate their research and education programs so as to better address today's challenges.  The book is intended for use in academic, government, and industrial R&D departments as a reference tool in research and technology education. The 40 peer-reviewed papers were written by more than 110 leading scientists from 14 countries, most of them affiliated to the I-AC.
Hydrothermal synthesis and characterization of mixed fluoride based nanophosphors -- Transfer of Light Energy from UV to Visible Domain in Coordination Compounds of Europium(III) -- Phase composition, structure and mechanical properties of carbon coatings doped by carbide-forming metals -- Ellipsometric Control of Laser Welded Materia -- Comparison of Euler-Bernoulli and Timoshenko Beam Equations for Railway System Dynamics --  Interaction of hydrogen isotopes with radiation damaged tungsten -- Reviewing the Novel Machine Learning Tools for Materials Design -- Sol-gel  preparation and luminescent properties of transparent thin films and ceramics of ZrO2:Ti3+ -- Development of functional coatings by electron-beam sputtering of sol-gel targets -- Omega-structured substrate-supported metamaterial for the transformation of wave polarization in THz frequency range -- Core-shell powders with titanium coating.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence